Effects of standalone plyometric training on vertical jump and linear sprint performance in handball athletes: a systematic review and meta-analysis - Zhang, C.; Wang, Q. (Frontiers in Physiology, 2026)
Introduction: Handball is a high-intensity intermittent sport that demands exceptional lower-body explosive power for jumping and sprinting in match play. Existing research on plyometric training for handball athletes often combines this modality with other interventions, leaving the independent effects of standalone plyometric training on key physical outcomes poorly quantified. This meta-analysis aimed to systematically evaluate the efficacy of standalone plyometric training on vertical jump (squat jump [SJ], countermovement jump [CMJ]) and multi-distance linear sprint performance in handball athletes, and to explore moderators of training response.